2015
DOI: 10.1136/bmjopen-2014-007167
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of nurse practitioners in primary and specialised ambulatory care: systematic review

Abstract: ObjectiveTo determine the cost-effectiveness of nurse practitioners delivering primary and specialised ambulatory care.DesignA systematic review of randomised controlled trials reported since 1980.Data sources10 electronic bibliographic databases, handsearches, contact with authors, bibliographies and websites.Included studiesRandomised controlled trials that evaluated nurse practitioners in alternative and complementary ambulatory care roles and reported health system outcomes.Results11 trials were included. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
174
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(207 citation statements)
references
References 38 publications
7
174
0
1
Order By: Relevance
“…22 Furthermore, evidence shows that nurse practitioners in primary care professional roles have equivalent or superior patient outcomes and are potentially cost saving. 42 This finding suggests the potential of nurse practitioner-physician comanagement to be more cost effective than 2 physicians comanaging care. More cost-effective studies about nurse practitionerphysician comanagement are warranted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Furthermore, evidence shows that nurse practitioners in primary care professional roles have equivalent or superior patient outcomes and are potentially cost saving. 42 This finding suggests the potential of nurse practitioner-physician comanagement to be more cost effective than 2 physicians comanaging care. More cost-effective studies about nurse practitionerphysician comanagement are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…42 This finding suggests the potential of nurse practitioner-physician comanagement to be more cost effective than 2 physicians comanaging care. More cost-effective studies about nurse practitionerphysician comanagement are warranted.…”
mentioning
confidence: 99%
“…Few studies, however, have compared APCs and physicians specifically in providing inefficient or low-value care. The existing literature is limited and shows mixed results, with some studies showing increased value and others showing no net change or lower value associated with APCs (15, 34, 35). Moreover, these studies focused mainly on health care costs, and few investigated the use of guideline-discordant and low-value health services as we did in our study.…”
Section: Discussionmentioning
confidence: 99%
“…There is a discrepancy of perspectives, however, regarding NP reimbursement rates, hospital admitting privileges and having a NP lead a medical home (Donelan, DesRoches, Dittus, & Buerhaus, 2013). For example, a recent systematic review found potential for cost savings when NPs complement physician-based care (Martin-Misener et al, 2015). Yet, while the American College of Physicians (ACP) (2009) supports the expansion of NP scope of practice to help alleviate the strain in primary care, other medical organizations firmly believe that primary care patients should be strictly physician-managed (American Academy of Family Physicians, 2012).…”
Section: Introductionmentioning
confidence: 99%